Revisionsbyråers kommunikation av AI-användning: En studie om imagebyggande i externa kanaler - Osman,Ahmed; Bengtsson,Johanna; Palac,Filip (2025)
Abstract Title: Auditing Firms’ Communication of AI Use: A Study on Image Construction in External Channels Seminar date: June 3 2025 Course: FEKH69 Authors: Johanna Bengtsson, Ahmed Osman and Filip Palac Advisor: Elin Funck Key words: Auditing, Artificial intelligence (AI), Strategic communication, External Communication Research question: How do auditing firms communicate their use of AI in external channels, and what image are they trying to create through this communication? Purpose: The purpose of this study is to increase understanding of how auditing firms in Sweden communicate their use of AI in external channels, and what image they aim to convey through this communication. Methodology: A qualitative document analysis was conducted on websites and annual/sustainability reports from eight auditing firms. The material was thematically analyzed using an abductive approach, where coding formed the basis for identifying communicative patterns. Theoretical Perspectives: The study is based on Gray and Balmer’s (1998) theory of image, Blair-Loy et al.’s (2011) concept of strategic communication, and Abrahamson’s (1996) theory of management fashion. These were combined into an analytical model to interpret the role of AI communication in image construction. Results: Audit firms’ external AI communication is used strategically to signal technical 4 competence, future orientation, and responsibility, creating an image that does not always reflect actual AI use. Communication strategies vary primarily with the business model and the extent of communication, rather than the firm’s size. AI therefore serves as a positioning marker, where some firms appear as trend setters and others as trend followers, depending on how they relate to innovation, norms, and expectations. Conclusion: AI communication is not primarily used to disclose actual usage, but rather to strategically shape an intended image in a transforming industry. By balancing innovation with ethical responsibility, firms position themselves to meet both market expectations and regulatory demands. Even the absence of AI communication can be interpreted as a deliberate strategic choice, indicating uncertainty about the technology or a lack of genuine integration into operations.